Direct homocysteine biosynthesis from O-succinylhomoserine in Escherichia coli: an alternate pathway that bypasses cystathionine. - Simon, M (1983)
Mutations were found which enable Escherichia coli K-12 to form homocysteine in the absence of cystathionase. The formation of homocysteine in the mutant strains required cystathionine gamma-synthetase, the metB gene product, but bypassed the normal intermediate cystathionine. It is concluded that cystathionine gamma-synthetase catalyzes the formation of homocysteine directly from O-succinylhomoserine and an as-yet-unidentified sulfur donor. The mutation apparently causes the formation of this sulfur donor and has been named metQ. The expression of the metQ gene is under catabolite repression.